Analytical fragility curves for assessment of the seismic vulnerability of HP/HT unburied subsea pipelines. Issue 137 (October 2020) - Mina, Daniele; Forcellini, Davide; Karampour, Hassan
Abstract: Vulnerability of subsea high pressure/high temperature (HP/HT) pipelines to seismic actions is studied numerically. Unlike most of the existing researches on buried or trenched pipelines, this study is focused on the response of an unburied pipeline with D/t  = 20, laid on the seabed and resting on a sleeper. Two different scenarios: (1) earthquake imposed on a laterally buckled pipeline, and (2) earthquake imposed at temperatures lower than the lateral buckling temperature, are studied. The onset of yield and development of compressive local wrinkles in the wall thickness are calculated as the failure modes. Analytical fragility curves are developed based on probability of exceedance of the failure limits for each scenario. It is understood that the pipeline in scenario 1 is more vulnerable to bending-induced damages. Highlights: Seismic response of a HP/HT subsea pipeline on a sleeper is studied numerically. Possible interaction between lateral buckling (LTB) and earthquake (EQ) actions are evaluated. Two different scenarios are investigated (1) LTB then EQ, and (2) EQ before LTB. Analytical fragility curves are developed based on probability of exceedance of the failure limits for each scenario. It is understood that the pipeline in scenario 1 is more vulnerable to bending-induced damages.